(:unas) unassigned - Mettas, Christodoulos (My University, 2018)
Project Title: Residential Development in Gladstonos Street, Nicosia. The project involved the building of four houses and thirty flats. All of the units were served by an underground parking. Responsibilities as a trainee engineer were: 1. Supervision of the project and reporting to the engineers. 2. Surveying tasks (levelling and setting out). 3. Use of the detailed drawings to estimate quantities of some materials that were to be used in the Bill of Quantities. 4. Miscellaneous civil engineering work on the computer